Extracranial complications of chronic suppurative otitis media - Hossain, MM; Kundu, SC; Haque, MR; Shamsuzzaman, AK; Khan, MK; Halder, KK (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):4-9 The abstract of this article is available on the PubMed website